2020
DOI: 10.1080/15513815.2020.1828517
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Third Trimester Placenta from SARS-CoV-2-Positive Women

Abstract: Background: This study aims to investigate whether maternal SARS-CoV-2 status affects placental pathology. Methods: A retrospective case-control study was conducted by reviewing charts and slides of placentas delivered between April 1 to July 24, 2020. Clinical history of "COVID-19" was searched in Pathology Database (CoPath). Controls were matched with SARS-CoV-2-negative women with singleton deliveries in the 3 rd-trimester. Pathological features were extracted from placental pathology reports. Results: Twen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Our findings are consistent with Hecht et al, 23 Gulerson et al, 35 and He et al 36 The first of the aforementioned studies, found no characteristic histopathologic findings in 19 placentas from women with proven SARS-CoV-2 infection, despite RNA evidence of the virus in syncytiotrophoblast in two of the cases. 23 Gulerson et al examined 50 placentas from women diagnosed with SARS-CoV-2 in the third trimester and found no difference in the prevalence of various placental pathology between women with and without SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with Hecht et al, 23 Gulerson et al, 35 and He et al 36 The first of the aforementioned studies, found no characteristic histopathologic findings in 19 placentas from women with proven SARS-CoV-2 infection, despite RNA evidence of the virus in syncytiotrophoblast in two of the cases. 23 Gulerson et al examined 50 placentas from women diagnosed with SARS-CoV-2 in the third trimester and found no difference in the prevalence of various placental pathology between women with and without SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 93%
“…Herein we report no relevant differences in placental histopathologic patterns between SARS-CoV-2 infected pregnant women and non-infected controls with similar maternal characteristics. Previous studies have also suggested no specific histopathologic differences in placentas from infected patients [ 14 , 15 , 16 , 17 , 18 , 19 ], but these reports were lacking appropriately selected controls group.…”
Section: Discussionmentioning
confidence: 97%
“…Several authors suggest that COVID-19 may trigger a severe systemic inflammatory response, with consequent MVM caused by the SARS-CoV-2 infection derived-hypoxia [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. We also recently reported [ 32 ] evidence of an increased immune activation profile in SARS-CoV-2 positive subjects, with higher levels of cytokines and chemokines in placental tissue, maternal and funicular plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of researchers stated that the SARS-CoV-2 localized predominantly in STBs, 36 but despite that, they reported that there was no statistically significant difference in placental histopathological evaluations through the placentas of COVID-19 positive women following the second opinion mentioned above. [37][38][39]…”
Section: Zhang Et Al Examined 74 Placentas and Tested Placental Tissuesmentioning
confidence: 99%